The plague - Camus, Albert, 1913-1960.; Gilbert, Stuart (London : Penguin Books, 2002)
A coastal city in Algeria is struck by bubonic plague and is shut off from the world for months.
Translation of: La peste.
Adult.
Adult
Keywords: Plague -- Fiction; Plague -- Fiction; Algeria -- Fiction; Algeria -- Fiction